Efficiency maximization of resonant coupled wireless power transfer system via impedance matching based on coupling tuning - Barman, S.D.; Reza, A.W.; Kumar, N. (2014)
Non-radiative wireless power transfer (WPT) system using strong magnetic resonant coupling has been recently proposed and has shown more prospects in mid-range wireless power transmission due to its operating range and efficiency. The efficiency of such WPT system changes with the coupling distance between the coils changes, which is a critical issue for high efficient power transmission. In this paper, we demonstrate an impedance matching approach based on coupling tuning to enhance and maximize the efficiency of the system. The matching conditions are derived by analysing an equivalent circuit model of the system using reflected load theory (RLT) along with the derivation of maximum transmission efficiency. The matching condition is achieved by tuning coupling coefficients between the loop-coil and the internal coil, and verified against theoretical data by simulation in an electric automatic tool. Applying this technique results, efficiency of over 90% at the small coupling distance at a fixed operating frequency. The results show improvement of efficiency are about 16.1 % and 9.8 % at 90 cm and 1.15 m, respectively, compared to the traditional WPT system without matching, and thereby increase the operating range of the system.